Enhancement of durability and engineering performance of lightweight foamed concrete reinforced with alkali-treated coir fiber / Siti Nurain bZainal Afandi and Md Azree Othuman Mydin - Zainal Afandi, Siti Nurain; Othuman Mydin, Md Azree (2018)
With regards to environmental concerns and in line with Malaysian government's environmental strategy on utilizing sustainable waste materials such as those from natural resources in turn to diminish the harmful effects of synthetic materials on the environment, it has brought a challenge to reconnoiter how it can be attained by promoting the agricultural wastes into useful products. Hence this research attempts to investigate the potential use of coir fiber as reinforcement material in lightweight foamed concrete. The effect of alkali treatment of coir fiber at different percentages of 2%, 4%, 6%, 8% and 10% wt. concentration were investigated comprehensively. Experimental results showed that alkali treatment of coir fiber plays an important role to alter the interface of the fiber adequately prompting a variation in the durability and mechanical properties holistically. As a whole, 6% of alkali treatment of coir fiber is the optimum percentage in which it gave the highest compressive strength and splitting tensile strength. The significance of alkali treatment of coir fiber was the meddling of hydrogen bonding in the fiber surface, consequently increasing the surface roughness as well. This condition is really beneficial for coir fiber and the cement matrix interfacial adhesion as a rougher surface expedites fiber and cement matrix mechanical interlocking.